Stained glass windows in British churches and cathedrals.
Places and buildings include: stained glass windows from Mark Church, ?Halifax; Trinity Church, Reading; Mary Slessor memorial window, Dundee; Liverpool Cathedral. Prints taken by: Mr C W Hill; Golderstat, 95 Cambridge Road London NW6; E N Ellis; Rasmus R Madsen, Liverpool; Heswall Bevan.